Comparative Efficacy and Toxicity of Different Species of Sargassum in Haizao Yuhu Decoction in PTU-Induced Goiter Rats. (21st June 2017) - Xiu, Linlin; Zhong, Gansheng; Liu, Dianna; Chen, Shaohong; Liu, Haiyan; Chen, Feng
Abstract : Background . Haizao Yuhu Decoction has been widely used to treat thyroid-related diseases especially goiter with few side effects in traditional Chinese medicine (TCM), including herb pair Sargassum (HZ) and Glycyrrhizae Radix et Rhizoma (GC), as one of "eighteen antagonistic medicaments." The two different species of Sargassum, Sargassum fusiforme (Sf) and Sargassum pallidum (Sp), are not clearly differentiated in clinical use, so that herb pair Sf-GC and Sp-GC could show different effect and toxicity. Methods . We investigated the antigoitrous effect and toxicity and clarified the potential underlying mechanism of the two different species of Sargassum in HYD (HYDf and HYDp) in PTU-reduced goiter rats. Results . The results demonstrated that both HYDf and HYDp could exhibit antigoitrous effect through alterations in hypothalamus-pituitary-thyroid (HPT) axis and inhibition of the TPO gene expression; there is no difference in the antigoitrous effects between the two different species of Sargassum application in HYD. Conclusion . This study evaluated the safety and efficacy of herb pair HZ-GC applied in HYD in goiter rats at molecular, cellular, and whole level and compared the two species of Sargassum further. We provide a reliable way to clarify the possible mechanism of the antagonistic medicament herb pair HZ-GC for its application.